Lifestyle of patients with peripheral arterial occlusive disease undergoing surgical revascularization procedures - Spannbauer, Anna; Madejczyk, Monika; Chwała, Maciej; Berwecki, Arkadiusz (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2015)
Peripheral arterial occlusive disease (PAOD) is a condition cauPeripheral arterial occlusive disease (PAOD) is a condition caused by narrowing or occlusion of the arterial lumen, which results in claudication. Patients with advanced stages of disease, that is short claudication distance, rest pain or ischaemic ulcerations are often qualified for surgical procedures of vascular prosthesis in order to bypass the damaged artery. Peripheral arterial occlusive disease is accelerated by unhealthy lifestyle. Aim of the study: The aim of the study was to assess the lifestyle of the patients with PAOD in terms of diet, physical activity and smoking and whether it needs modification. Material and methods : One hundred and four patients with PAOD IIB, III and IV according to Fontaine’s scale who underwent the bypass procedure were included in the study. Results: 80.7% of patients were smoking prior to the operation for more than 5 years. 100% of patients were informed by their family doctor or vascular surgeon about necessity to modify the risk factor such as smoking, diet and lack of physical activity. Only 9.6% of patients gave up smoking after the operation. 75% of patients who exercise claim to do it for 15 minutes daily. The same percentage of patients remain either obese or overweight. 38.4% of respondents state that physical activity has no influence on health. Conclusion : Majority of patients with advanced PAOD ignore the recommendations of healthy lifestyle concerning smoking, diet and physical activity. Apart from family doctors and vascular surgeons, lifestyle education should be provided primarily by nurses and physiotherapists.